2015
DOI: 10.1259/bjr.20140730
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the CT localizer radiograph: acquisition parameters, patient centring and their combined influence on radiation dose

Abstract: Objective: To systematically investigate the effect of CT localizer radiograph acquisition on the tube current modulation and thus radiation dose of the subsequent diagnostic scan. Methods: Localizer radiographs of an abdominal section CT phantom were taken, and the resulting volume CT dose index (CTDIvol) for the diagnostic scan was recorded. Variables included tube potential, the phantom's alignment within the CT scanner gantry in both the vertical and horizontal directions and the X-ray source angle at whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 15 publications
1
14
0
Order By: Relevance
“…Our observations indicate that, despite trying to vertically center the phantom as accurate as possible, the attenuation centering was on average too low. Similar findings according to the patient vertical centering were previously reported (9,11,17).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our observations indicate that, despite trying to vertically center the phantom as accurate as possible, the attenuation centering was on average too low. Similar findings according to the patient vertical centering were previously reported (9,11,17).…”
Section: Discussionsupporting
confidence: 91%
“…Some studies suggested that the use of a PA instead of an AP projection for localizer radiography may lead to higher tube currents and, thus, to an increased radiation dose at the CT examination (8,9). However, these studies estimated radiation doses from the CT examination only and did not take into account the dose from localizer radiography as well.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The apparent object size may be misinterpreted on the localizer radiograph as the system assumes the object is at the isocenter, and implementation of the TCM would be adjusted accordingly (10) . With the object centered below the isocenter, the object's size is estimated to be smaller than the actual size.…”
Section: Resultsmentioning
confidence: 99%
“…Parakh et al decision software solutions (18,19). After a rigorous review of justification of each scan, radiologists should ensure that patients undergo scanning that is in accordance with the ALARA (as low as reasonably achievable) principle, which is practically done by optimizing each examination through proper patient centering, judicious use of intravenous contrast material, and selecting suitable technical parameters (20)(21)(22). CT manufacturers have also played a critical role by focusing on the development of effective technologies for dose reduction (automatic tube current modulation, iterative reconstruction techniques, dynamic collimation, and dose-efficient detectors), while preserving diagnostic accuracy and image quality (23)(24)(25)(26)(27)(28).…”
Section: How I Do It: Ct Radiation Dose Managementmentioning
confidence: 99%